Real-time 3D character animation with Visual C++. - Lever, Nik, ....- (Oxford : Focal, 2002)
Do you have some experience and a reasonable knowledge of C++ and want to write your own computer games? Have you ever looked at a PC or Playstation (R) game with characters running and leaping through an exciting landscape and wondered how it was done? If so then this book will give you all the information you need to achieve this goal, whether you are a hobby programmer, student or even a professional wanting to add that third dimension to your website. Nik Lever takes you through the journey from the basics of 3D manipulation all the way to morph objects and sub-division surfaces. On the way you get Visual C++ project files to study and software that runs on the Windows desktop. The free CD-ROM gives you a full-featured development environment for 3D character animation, so even if you find some of the maths and the code hard to follow straight away you can still create your own games. The game engine (Toon3DCreator) provided free and fully functional on the CD-ROM, even has an ActiveX control that allows you to distribute your work on the Internet. All source code for Toon3D is included on the CD. You will also get an insight into the artist's problems; learn how to keep the characters interesting while not exhausting the game engine. Understand the complete picture and make the most of your skills to help you succeed in, or break into the computer gaming industry with this comprehensive guide to programming for real-time 3D character animation.
Keywords: Computer graphics